Rasch Analysis of the Japanese Version of Teacher Efficacy for Inclusive Practices Scale: Scale Unidimensionality - Alnahdi, Ghaleb H.; Yada, Akie (Frontiers in Psychology, 2020)
This study aimed to examine the construct validity of the Japanese version of the Teacher Efficacy for Inclusive Practices (TEIP) scale. The sample consisted of 250 teachers in Japan. Rasch analysis was used to examine the psychometric properties of the scale. Results did not support the 18-item Japanese version of the TEIP scale as a unidimensional scale for measuring teacher efficacy for inclusive practices. However, they do support the final 14-item Japanese version of the TEIP scale as a unidimensional scale for measuring teacher efficacy for inclusive practices. Four items were removed from the original 18-item scale (items 12, 8, 5, and 3) for violation of the local independency assumption. No item with differential item functioning was detected. Only one item (item 18) was rescored to solve a threshold disorder. Further studies with different samples are warranted to confirm the study findings.